PENGARUH STANDART SARANA DAN PRASARANA TERHADAP EFEKTIFITAS PEMBELAJARAN DI TK AL-FIRDAUS - Nurhafit - Kurniawan (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2018)
This research entitled "Influence standard of facilities and infrastructure to the effectiveness of learning in Kindergarten Al-Firdaus "the problem discussed in this research is how much influence the means of prasana to KBM process that exist in kindergarten Al pardaus, purpose of this research to know influence of facility and infrastructure to effectiveness KBM TK Al Firdaus. Methods in the study using descriptive correlational analysis, Vareabel Implementation of Standard Means and Infrastructure (X) is one of the resources that must be managed and improved continuously along with the development of science and technology, Vareabel Learning Effectiveness (Y) a deliberate, purposive, and controlled effort in order for others to learn or relative permanent change in others / or institution / kindergarten Alfirdaus, data processing in this study using statistical methods assisted excel program 2007 and SPSS 17.0. Based on the results of research data obtained through a questionnaire-shaped instrument, then given a score on each alternative answers given by the respondent in accordance with the weight that has been set. Each statement in the three variables has 5 answer criteria with scoring starting from 1, 2, 3, 4, and 5 with terms for statements calculated with the results of descriptive calculations. Classroom conditions in kindergarten Al-Firdaus 13.33% - 26.67% in lightly damaged condition, while the rest is very suitable to use. Learning media such as props, learning etc. are also complete, which is very concerned is the school computers that achieve 40-60% damage even more inadequate amounts are also specifications that lag far behind. Based on the research results can be concluded that one effort that can be done to improve the Effectiveness of Learning in kindergarten Al Firdaus is by improving facilities and infrastructure.